Species composition, abundance and distribution of Chaetognaths in Southern Peninsula - Ranises, Dina Mae L.
The species composition, abundance and distribution of cheatognaths in Southern Zamboanga Peninsula were studied based on samples from 8 stations collected during an oceanographic cruise from March 4-8, 2014. Of the 1,600 chaetognaths examined, 19 species from 3 genera were identified. Sagitta enflata was the most common and abundant species, comprising about 27.1% of the total chaetognaths. The overall mean density was 12.4 ind.m-3 with values ranging from 5.2 to 22.5. High chaetognaths densities were observed in stations located in the northern transect with the highest density value located in the middle station. This is attributed to upwelling, as typically indicated by elevated by elevated chlorophyll a concentrations and low temperature. On average, densities in the Southern stations were almost two times lower than those in the northern stations. The presence of mesopelagic species (Sagita decipiens and Sagitta zetesios) in the sample collected from the station located within the upwelling area is consistent with vertical transport of deeper water. Similarly, the presence of the neritic species Sagitta bedfordii in the samples collected from an offshore station could indicate the movement of water offshore as a result of Ekman transport. The overall Shannon diversity (H?) value in the study area was 1.7 with values ranging from 1.13 to 2.06. A t-test found the difference in diversity values between the northern and southern transect to be highly significant (P<0.05). Highest diversity was observed within the upwelling area. The low species richness and diversity in the southern stations may be attributed to the dominance of Sagitta septata. Juvenile specimens constitute the bulk of the population in the northern stations while mature Sagitta septata individuals dominate the southern stations. The results of this study could be used as baseline information in understanding the dynamics of water movement along the Zamboanga peninsula and also to further monitor the dynamics of plankton assemblages which clearly affects the fishery production in the area.